CARBON ABSORPTION ANALYSIS THROUGH ORGANIC-C CONTENT IN SEDIMENT AT AMPEKALE MANGROVE ECOSYSTEM, MAROS REGENCY - Rukminasari, Nita; Sarwinda, Sarwinda; Suwarni, Suwarni; Moka, Wilma Joanna Carolina (Jurnal Ilmu Kelautan SPERMONDE, 2025)
Global warming represents a significant challenge, primarily driven by the escalating concentrations of greenhouse gases in the atmosphere, notably carbon dioxide (CO₂). Mangrove ecosystems are integral to climate change mitigation due to their capacity to sequester and store carbon within their biomass and sediment. This study sought to evaluate carbon sequestration through the analysis of organic carbon content in the sediments of mangrove ecosystems located in Ampekale, Maros Regency. Sampling was executed using a purposive sampling method across nine sites, employing a 50 × 5 cm corer. Each sediment sample was sectioned into five depth intervals (0-10 cm, 10-20 cm, 20-30 cm, 30-40 cm, and 40-50 cm). The organic carbon content was assessed using the loss on ignition (LOI) method, with parameters measured including bulk density, sediment organic carbon concentration, carbon storage, and carbon uptake in sediments. Statistical analyses were conducted utilizing one-way and two-way ANOVA tests. The findings indicated that the mangrove ecosystem in Ampekale exhibited a total carbon storage in sediments of 731.72 tons/ha, with a total carbon uptake of 2685.42 tons/ha. The greatest carbon storage and uptake were observed at the 40-50 cm depth, with values of 342.056 tons/ha and 1255.34 tons/ha, respectively.